Progression of Amyloid Pathology to Alzheimer's Disease Pathology in an Amyloid Precursor Protein Transgenic Mouse Model by Removal of Nitric Oxide Synthase 2 - Wilcock, Donna M. (Society for Neuroscience, 2008)
Alzheimer's disease (AD) is characterized by three primary pathologies in the brain: amyloid plaques, neurofibrillary tangles, and neuron loss. Mouse models have been useful for studying components of AD but are limited in their ability to fully recapitulate all pathologies. We crossed the APPSwDI transgenic mouse, which develops amyloid β (Aβ)-protein deposits only, with a nitric oxide synthase 2 (NOS2) knock-out mouse, which develops no AD-like pathology. APPSwDI/NOS2(−/−) mice displayed impaired spatial memory compared with the APPSwDI mice, yet they have unaltered levels of Aβ. APPSwDI mice do not show tau pathology, whereas APPSwDI/NOS2(−/−) mice displayed extensive tau pathology associated with regions of dense microvascular amyloid deposition. Also, APPSwDI mice do not have any neuron loss, whereas the APPSwDI/NOS2(−/−) mice have significant neuron loss in the hippocampus and subiculum. Neuropeptide Y neurons have been shown to be particularly vulnerable in AD. These neurons appear to be particularly vulnerable in the APPSwDI/NOS2(−/−) mice as we observe a dramatic reduction in the number of NPY neurons in the hippocampus and subiculum. These data show that removal of NOS2 from an APP transgenic mouse results in development of a much greater spectrum of AD-like pathology and behavioral impairments.